Ribociclib-Induced Pseudo-Acute Kidney Injury. Issue 1 (June 2022) - Sy-Go, Janina Paula T.; Yarandi, Niloufarsadat; Schwartz, Gary L.; Herrmann, Sandra M.
The combination of endocrine therapy and cyclin-dependent kinase (CDK) 4/6 inhibitors is currently one of the preferred first-line regimens for patients with hormone receptor (HR)-positive, human epidermal growth factor receptor 2 (HER2)-negative advanced or metastatic breast cancer. CDK 4/6 inhibitors can cause serum creatinine (SCr) elevation and corresponding estimated glomerular filtration rate (eGFR) reduction without affecting kidney function by inhibiting tubular secretory transporters in the kidneys—a phenomenon called pseudo-acute kidney injury (pseudo-AKI). We report a case of a 69-year old woman found to have elevated SCr while on ribociclib for treatment of metastatic breast cancer. Further evaluation with cystatin C-based eGFR and measured GFR by urinary iothalamate clearance revealed values close to her baseline Cr-based eGFR prior to initiation of treatment with ribociclib. She was therefore diagnosed with ribociclib-induced pseudo-AKI. Treatment with ribociclib was continued with steady favorable response. This case highlights that, in addition to true AKI, ribociclib can cause pseudo-AKI. Alternative methods of kidney function assessment may be necessary in patients who develop elevated SCr while on this medication to help discriminate between artifactual and true kidney function impairment. Doing so can help avoid unnecessary work-up and/or premature discontinuation of the treatment.